Data Analytics and Prediction Model for Malaysian Covid 19 Vaccination Progress - Gophinath Krishnan; M. Reyasudin Basir Khan (Malaysian Journal of Science and Advanced Technology, 2022)
SARS CoV-2 varieties keep developing, triggering disease outbreaks and delaying or even halting the opening of society and economies. In countries with high vaccination rates, there have been significant decreases in serious illness, hospitalization, and mortality. Nevertheless, vaccine availability is unequal internationally, with coverage varying from 1% to over 70%, primarily dependent on the nation's income. This study focuses on conducting data analytics and prediction model on the impact and intensity of the Covid-19 global vaccination trend compared to Malaysia. The country's vaccination performance is compared and analyzed with G7 countries such as Canada, France, Germany, Italy, Japan, the United Kingdom, and the United States. Moreover,  the vaccination rate of Malaysia and several SEA countries have also been compared in this study. This study discusses vital information such as the type of vaccines and vaccination rates. Meanwhile, the prediction model's goal is to predict the country's future vaccination trend.